The type material of Mordellidae described by Achille Costa (Coleoptera: Tenebrionoidea) - Selnekovič, Dávid; Improta, Roberta (Zootaxa, 2020)
A complete list of the type material of Mordellidae described by Achille Costa is provided. Mordellistena picipes Costa, 1854 stat. restit. is restored as a valid species and a diagnostic description of the lectotype is given. Natirrica meridionalis Costa, 1854 is proposed as a new synonym of Mordellistena humeralis (Linnaeus, 1758). Lectotypes and paralectotypes are designated for the following taxa: Tomoxia bucephala Costa, 1854; Mordella coronata Costa, 1854 (= Variimorda villosa (Schrank, 1781)); M. interrupta Costa, 1854 (= Variimorda villosa (Schrank, 1781)); M. brevicauda Costa, 1854 (= M. brachyura Mulsant, 1856); M. perspicillata Costa, 1854 (= Mediimorda bipunctata Germar, 1827); M. viridescens Costa, 1859; Variimorda basalis (Costa, 1854); Mordellistena stricta Costa, 1854 (= M. pumila (Gyllenhal, 1810)); M. picipes Costa, 1854; M. confinis Costa, 1854; M. minima Costa, 1854; Natirrica meridionalis Costa, 1854 (= Mordellistena humeralis (Linnaeus, 1758)). The male genitalia of the Variimorda basalis lectotype are illustrated here for the first time. Photographs of the labels are provided for the type specimens.